The Role of Accounting Information in Improving Financial Performance in Commercial Banks: A Field study at North Bank - Bakhcha Abdullah Muhammad; Rizgar Ali Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
n light of technological progress, accounting has become of great importance, especially for accounting information, as the accounting information system provides information to internal and external parties, and the accounting information has great importance in directing and rationalizing the decisions on which the decision-maker relies. It is related to obtaining funds and using them effectively, which is the main tool in support of all the activities of the various economic unit, improving production efficiency and reducing costs. Therefore, this research aims to know the importance of accounting information and how to rely on it to improve financial performance in commercial banks, To achieve the objectives of the research, the questionnaire form was formed and distributed to a number of employees working in North Bank and the use of spss program to analyze the data, and the study reached a set of conclusions as follows: Financial statements are the most important information as the primary source for evaluating financial performance so they must have qualitative characteristics that help to make important decisions to improve financial performance. 2 - Accounting information systems integrate the functions of the institution, which helps the smooth functioning of the bank to improve its financial performance. 3- There is a strong direct relationship between the accounting information axis and the axis of improving financial performance. 4 - There is a strong and direct relationship (accounting information used in commercial banks).